2016
DOI: 10.1038/srep21925
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal Antibody Production for Membrane Proteins via Genetic Immunization

Abstract: Antibodies are essential for structural determinations and functional studies of membrane proteins, but antibody generation is limited by the availability of properly-folded and purified antigen. We describe the first application of genetic immunization to a structurally diverse set of membrane proteins to show that immunization of mice with DNA alone produced antibodies against 71% (n = 17) of the bacterial and viral targets. Antibody production correlated with prior reports of target immunogenicity in host o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 65 publications
(89 reference statements)
0
39
0
Order By: Relevance
“…This method allows the transfer of a foreign gene quickly and reliably. It can also be used to produce an antibody specifically against a protein without many purification steps [24]. We previously reported that antibodies produced by genetic immunization using human nephrin DNA had high specificity [25,26].…”
mentioning
confidence: 99%
“…This method allows the transfer of a foreign gene quickly and reliably. It can also be used to produce an antibody specifically against a protein without many purification steps [24]. We previously reported that antibodies produced by genetic immunization using human nephrin DNA had high specificity [25,26].…”
mentioning
confidence: 99%
“…We recently reported the first description of the efficiency of any DNA immunization approach specific for membrane proteins (Hansen et al, 2016). We applied the DNA-gold micronanoplex method (Svarovsky et al, 2009) and the immunization vector pCMVi-LSrCOMPTT (Table 1; Figure 1) to a structurally diverse set of 17 membrane proteins from two Biosafety Level 3 pathogens, and demonstrated polyclonal antibody production for more than half of the targets (Hansen et al, 2016).…”
Section: Strategic Planningmentioning
confidence: 99%
“…We applied the DNA-gold micronanoplex method (Svarovsky et al, 2009) and the immunization vector pCMVi-LSrCOMPTT (Table 1; Figure 1) to a structurally diverse set of 17 membrane proteins from two Biosafety Level 3 pathogens, and demonstrated polyclonal antibody production for more than half of the targets (Hansen et al, 2016). A major validation of this study was that antibody production correlated with prior reports of target immunogenicity in infected or immunized hosts (Hansen et al, 2016). To support widespread use, all plasmid vectors from this study have been made available through the non-profit DNASU Plasmid Repository (Seiler et al, 2014).…”
Section: Strategic Planningmentioning
confidence: 99%
See 2 more Smart Citations